Faktor Investasi Klasik Peserta Asuransi pada Unit Link Syariah di Yogyakarta - Zahirotul Kamiliyah (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
This research aimed to determine the classic investment factors for insurance participants on unit link Sharia in the Yogyakarta area. This research type used mixed method research (the quantitative and qualitative research). Primary data was obtained by distributing questionnaires, while the qualitative stage of data was obtained by interview, observation, and also documentation. The research results showed that classical investment factors could influence the participants' decision to invest in sharia unit link insurance. The effect is 3.0, i.e. participants stated